Effect of Estrogen on Heteronemin-Induced Anti-proliferative Effect in Breast Cancer Cells With Different Estrogen Receptor Status - Yang, Yu-Chen S. H.; Li, Zi-Lin; Huang, Tung-Yung; Su, Kuan-Wei; Lin, Chi-Yu; Huang, Chi-Hung; Chen, Han-Yu; Lu, Mei-Chin; Huang, Haw-Ming; Lee, Sheng-Yang; Whang-Peng, Jaqueline; Lin, Hung-Yun; et al. (Frontiers in Cell and Developmental Biology, 2021)
Estrogen (E2) has multiple functions in breast cancers including stimulating cancer growth and interfering with chemotherapeutic efficacy. Heteronemin, a marine sesterterpenoid-type natural product, has cytotoxicity on cancer cells. Breast cancer cell lines, MCF-7 and MDA-MB-231, were used for investigating mechanisms involved in inhibitory effect of E2 on heteronemin-induced anti-proliferation in breast cancer cells with different estrogen receptor (ER) status. Cytotoxicity was detected by cell proliferation assay and flow cytometry, gene expressions were determined by qPCR, mechanisms were investigated by Western blot and Mitochondrial ROS assay. Heteronemin exhibited potent cytotoxic effects against both ER-positive and ER-negative breast cancer cells. E2 stimulated cell growth in ER-positive breast cancer cells. Heteronemin induced anti-proliferation via suppressing activation of ERK1/2 and STAT3. Heteronemin suppressed E2-induced proliferation in both breast cancer cells although some gene expressions and anti-proliferative effects were inhibited in the presence of E2 in MCF-7 and MDA-MB-231 cells with a higher concentration of heteronemin. Heteromenin decreased the Bcl-2/Bax ratio to inhibit proliferation in MDA-MB-231 but not in MCF-7 cells. Both heteronemin and E2 increased mitochondrial reactive oxygen species but combined treatment reversed superoxide dismutase (SOD)s accumulation in MCF-7 cells. Heteronemin caused G0/G1 phase arrest and reduced the percentage of cells in the S phase to suppress cancer cell growth. In conclusion, Heteronemin suppressed both ER-positive and ER-negative breast cancer cell proliferation. Interactions between E2 and heteronemin in signal transduction, gene expressions, and biological activities provide insights into the complex pathways by which anti-proliferation is induced by heteronemin in E2-replete environments.